A critical review on the simulation of ultra-short pulse laser-metal interactions based on a two-temperature model (TTM). (April 2023) - Song, Shijie; Lu, Qinghua; Zhang, Peilei; Yan, Hua; Shi, Haichuan; Yu, Zhishui; Sun, Tianzhu; Luo, Zhirong; Tian, Yingtao
Highlights: We review the important theory of the laser-induced material formation of periodic micro-nanostructures. The physical processes of interaction between ultrashort pulse laser and materials are reviewed in this paper. The principle of two-temperature simulations is introduced and discussed thoroughly by the two-temperature model. Review and discuss seven typical complex simulations based on a two-temperature model. Abstract: The generation of periodical micro-nanostructures by laser-induced materials with ultrashort pulses has been a research hotspot in recent years and has been used extensively in many fields. There is a lot of research being done on laser-induced periodic surface structures (LIPSS, ripple) in the areas of navigation, medicine, aerospace, biology, etc. The study of laser ablation is greatly influenced by the intricate physical process of interaction between an ultrashort pulse laser and the material. In order to more successfully conquer this challenge, this paper reviews the ultrashort pulse laser ablation, induced material surface formation of periodic surface structure important theory, including the electromagnetic theory and matter reorganization theory. By summarizing the complex physical processes of ultrashort pulse laser ablation, review the most popular two-temperature model in contemporary ultrashort pulse ablation simulation. The effect of the two-temperature model on the development of ultrashort pulse laser technology is analyzed. By discussing using a two-temperature model to enhance the single-pulse laser ablation analysis and promote the understanding of the periodic micro-nano structures generated on the material's surface by ultrashort pulse laser ablation. This paper introduces a variety of complex two-temperature model methods to simulate the interaction between ultrashort pulse laser and metal. The main difficulties faced by ultrashort pulse laser processing are listed, and suggestions for simulation of ultrashort pulse laser processing in the future are put forward.